TEKNOLOGI PENGOLAHAN DAN APLIKASI PAKAN SILASE, KELOMPOK TERNAK TANI PHILADELPIA OESAO KABUPATEN KUPANG - Nancy D. F. K. Foeh; Frans Umbu Datta; Nemay Ndaong; Annytha Detha (Jurnal Media Tropika, 2021)
The Philadelphian farmer livestock group located in Oesao village, Kupang regency was one of the centers of agricultural and livestock development in the district. This is because it was supported by a source of livelihood for the people, namely agriculture so that the availability of agricultural waste such as corn and rice straw were abundant. The purpose of this service-learning was to optimize the empowerment of agricultural waste to increase the productivity of cattle from the Philadelphian farmer livestock group. Based on the results of this activity, it was seen that there was an increase in the knowledge of these farmer livestock groups. This service-learning was expected to be able to increase understanding and independence so that the availability of feed can continue to be fulfilled in the Philadelphian farmer livestock group, Oesao, Kupang NTT.